Blood pressure and lipid profiles in adolescents with hypertensive parents - Julia Fitriany; Rafita Ramayati; Supriatmo Supriatmo; Rusdidjas Rusdidjas; Oke Rina; Rosmayanti Siregar (Paediatrica Indonesiana, 2015)
Background Adolescent hypertension is a significant health problem of increasing prevalence and causes high morbidity and mortality. It is found primarily in young males, with a familial history of hypertension and/or cardiovascular disease. Examination of lipid profiles has been used to detect the risk of hypertension in adolescents. Objective To compare blood pressure and lipid profiles in adolescents with and without a parental history of hypertension. Methods This cross-sectional study was conducted from January to February 2012 on students from a senior high school in the Toba Samosir District, North Sumatera. Sixty-eight adolescents were included, aged 15 to 18 years. Group I comprised 34 adolescents with hypertensive parents, and group II comprised 34 adolescents with normotensive parents. Subjects were selected based on questionnaires. Subjects’ blood pressures were measured at rest. Three measurements were made in intervals of 10-15 minutes, then averaged for both systolic and diastolic blood pressures. Lipid profiles were measured using the CardioCheck cholesterol test after subjects had fasted for 12 hours. Results The median systolic blood pressures (SBP) in groups I and II were 110 mmHg (range 93.3-123.3) and 106.7 mmHg (range 96.7-123.3), respectively, (P=0.584). The median diastolic blood pressures (DBP) were 73.3 mmHg (range 66.7-83.3) and 71.7 mmHg (range 63.3-80.0), respectively, (P=0.953). Total cholesterol and low-density lipoprotein cholesterol (LDL-C) levels in group I were significantly higher than those levels in group II [median total cholesterol: 162.0 (range 158-170) vs. 159.0 (range 150-170), respectively; (P=0.001); and mean LDL-C: 103.5 (SD 3.72) vs. 99.1 (SD 4.63), respectively; (P=0.001). Multivariate analysis revealed a correlation of moderate strength between parental history of hypertension and increased LDL-C (P<0.001) in adolescents. Conclusion Adolescents with and without familial history of hypertension have no significant median blood pressure differences. However, adolescents with hypertensive parents have This study was presented at Pertemuan Ilmiah Tahunan V (PIT V/The 5th Child Health Annual Scientific Meeting) Bandung, October 15–17, 2012. From the Department of Child Health, University of Sumatera Utara Medical School/H. Adam Malik Hospital, Medan, North Sumatera, Indonesia. Reprint requests to: Dr. Julia Fitriany, Department of Child Health, University of North Sumatera Medical School/H. Adam Malik Hospital, Jl. Bunga Lau No.17, Medan 20136. Tel +6261 8361721 – +6261 8365663. Fax. +6261 8361721. E-mail: julia_fitriany@yahoo.com. Adolescent hypertension is an important health problem of increasing prevalence that affects morbidity and mortality.1 The prevalence of hypertension in adolescents has increased due to several factors such as obesity, a sedentary lifestyle, smoking, stress, sleep disorders and increased intake of high-calorie foods, sodium, alcohol, and caffeine.2 In the pediatric population, essential hypertension, also known as primary hypertension, mostly afsignificantly higher median total cholesterol and mean LDL-C. Furthermore, we find a correlation between parental history of hypertension and increased LDL-C in adolescents.